Belowground biodiversity and ecosystem functioning - Bardgett, Richard D.; van der Putten, Wim H. (Nature (London), 2014)
Growing evidence points to belowground biota as a significant contributor to aboveground diversity and functioning as well as impacting eco-evolutionary responses to environmental change; this review explores such evidence and proposes further research directions. Overground impact of underground biodiversity Belowground biodiversity is largely out of sight and mind, but there is mounting evidence to show that the vast diversity of subterranean microorganisms and animals that live belowground contribute significantly to shaping the overall biodiversity and and terrestrial ecosystem function. In this review, Richard Bardgett and Wim van der Putten consider recent work on the ecological and evolutionary role of belowground biodiversity and outline areas or research that would improve our understanding of the influence of soil biodiversity on the ecological and evolutionary responses of terrestrial ecosystems to environmental change. Evidence is mounting that the immense diversity of microorganisms and animals that live belowground contributes significantly to shaping aboveground biodiversity and the functioning of terrestrial ecosystems. Our understanding of how this belowground biodiversity is distributed, and how it regulates the structure and functioning of terrestrial ecosystems, is rapidly growing. Evidence also points to soil biodiversity as having a key role in determining the ecological and evolutionary responses of terrestrial ecosystems to current and future environmental change. Here we review recent progress and propose avenues for further research in this field.